COVID‐19 crisis and its impact on trustees and beneficiaries - YIP, Man (Institutional Knowledge at Singapore Management University, 2020)
The COVID-19 pandemic has been described by Prime Minister Lee Hsien Loong as the “crisis of our generation”. We have to swiftly adjust to a new “normal” characterised by safety measures, travel restrictions, economic downturn and uncertainties in the days ahead. What is the new “normal” for trustees and beneficiaries? How should they respond to the legal and practical uncertainties in these challenging times? This commentary discusses two categories of uncertainties for trustees and beneficiaries: (1) uncertainty relating to trust investments; and (2) uncertainty relating to day-to-day administration.